2015
DOI: 10.1021/acsnano.5b04231
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Hierarchical Surface Structures with Tunable Wettability for Regulating Bacteria Adhesion

Abstract: To circumvent the influence from varied topographies, the systematic study of wettability regulated Gram-positive bacteria adhesion is carried out on bioinspired hierarchical structures duplicated from rose petal structures. With the process of tuning the interfacial chemical composition of the self-assembled films from supramolecular gelators, the varied wettable surfaces from superhydrophilicity to superhydrophobicity can be obtained. The investigation of Gram-positive bacteria adhesion on the hierarchical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
172
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(178 citation statements)
references
References 65 publications
6
172
0
Order By: Relevance
“…Dou et al [186] recreated the topology of the rose petal using different polymer mixtures, and reported that the greatest adhesion of Gram-positive bacteria occurred at an intermediate hydrophobicity. Sousa et al [187] showed that bacteria grew better on superhydrophobic PLLA substrates when incubated with S. aureus or P. aeruginosa for 24 hours compared to flat PLLA surfaces (2-log reduction).…”
Section: Bacterial Interactionsmentioning
confidence: 99%
“…Dou et al [186] recreated the topology of the rose petal using different polymer mixtures, and reported that the greatest adhesion of Gram-positive bacteria occurred at an intermediate hydrophobicity. Sousa et al [187] showed that bacteria grew better on superhydrophobic PLLA substrates when incubated with S. aureus or P. aeruginosa for 24 hours compared to flat PLLA surfaces (2-log reduction).…”
Section: Bacterial Interactionsmentioning
confidence: 99%
“…Lubricant‐infused liquid‐repellency slippery surfaces possess outstanding antifouling properties that prevent adhesion of proteins, bacteria, cells, and marine organisms . Thus, liquid‐repelling surfaces have wide ranging applications in various fields such as textiles, water collection, corrosion control, chemical shielding, and environmental protection .…”
Section: Applicationsmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 as well as their effects on the microorganism structure and activity can be tailored by tuning their physicochemical characteristics. 10 In the case of bacteria and enveloped viruses, their lipid membrane constitutes an excellent target for deactivation since it is readily accessible.…”
Section: -8mentioning
confidence: 99%